Nitisastra as Reference for Tourist Guidance in Bali - Ida Bagus Nyoman Mertayasa (Bali Tourism Board, 2024)
One example of responsible tourism behavior is respecting local culture and traditions. This includes avoiding the dismissal of local customs, valuing and supporting the preservation of traditional arts, actively participating in the preservation and development of local traditions, and demonstrating a positive attitude and coexistence with others. At a minimum, tourists visiting various regions in Indonesia are expected to exhibit good tourism behavior. Gradually, this can set an example for other tourists, both domestic and international, who are also vacationing in Indonesia. The diversity of cultures (multiculturalism) is an inevitability that must be embraced by Indonesian society. Being a pluralistic and multicultural nation, Indonesia is susceptible to conflicts involving religion, culture, race, and customs. Such tensions often arise due to the intersection of diverse cultures, interactions between individuals and groups with differing perspectives, and varying levels of knowledge and understanding. The teachings of Nitisastra provide valuable insights into addressing these issues by emphasizing the importance of self-management, respect for knowledge, and ethical behavior. According to Nitisastra, the pursuit of knowledge and adherence to moral principles are central to responsible leadership and personal growth. For tourists, this translates into respecting local norms, practicing humility, and contributing to the welfare of the community. The Nitisastra perspective teaches that true wealth lies in knowledge and ethical conduct, which should guide interactions with local communities and the environment. These principles, when applied to tourism, can help mitigate the negative impacts of tourism and promote a more harmonious relationship between visitors and the local population.